Prospective evaluation of the impact of human papilloma virus status and small node size on the diagnostic accuracy of 18F‐fluorodeoxyglucose positron emission tomography/computed tomography for primary head and neck squamous cell carcinoma. Issue 7 (21st June 2020) - Lee, Jonathan; Emmett, Louise; Tang, Reuben; Ho, Bao; Earls, Peter; Matthews, Tim; Gallagher, Richard
Abstract: Background: Fluorodeoxyglucose‐positron emission tomography/computed tomography (FDG‐PET/CT) is well validated in the staging of pre‐treatment head and neck squamous cell carcinoma (HNSCC), although the impact of human papilloma virus (HPV) status and node size on accuracy remains unclear. The aim of this study was to assess the diagnostic accuracy of PET/CT based on HPV status and node size and determine the effects of maximum standardized uptake value thresholds on sensitivity, specificity and positive predictive value. Methods: A total of 38 patients with primary HNSCC were recruited. All patients underwent primary tumour resection and cervical node dissection following FDG‐PET/CT. Results: A total of 38 patients including 68 dissected necks, representing 353 nodal levels and a total of 2701 lymph nodes were included. Histopathological analysis revealed lymph node metastases in 4.3% (116/2701) of dissected lymph nodes. Forty‐four percent of patients had HPV‐positive tumours. Sixty‐four percent of involved lymph nodes were <1 cm. The sensitivity and specificity for HPV‐positive nodes were 67.2% and 99.3% versus 35.6% and 98.2% in HPV‐negative nodes, respectively ( P < 0.001). Mean maximum standardized uptake value in HPV‐positive nodes was 6.3 versus 3.5 in HPV‐negative nodes ( P < 0.001). Sensitivity and specificity were 30.7% and 99.2% in <1 cm nodes versus 90.2% and 84.8% in ≥1 cm nodes, respectively ( P < 0.001). Conclusion: FDG‐PET/CT has significantly higher diagnostic accuracy in determining nodal metastases in HPV‐positive HNSCC versus HPV‐negative disease. Accuracy was lower in <1 versus ≥1 cm nodes. Abstract : Staging of head and neck squamous cell carcinoma may be affected by node size and human papilloma virus (HPV) status. Our study ascertains the diagnostic accuracy of 18F‐fluorodeoxyglucose positron emission tomography/computed tomography with regards to these factors. It shows that subcentimetre nodes and HPV negativity are associated with decreased accuracy of 18F‐fluorodeoxyglucose.